Political corruption in the execution of public contracts - Olga Chiappinelli (Journal of Economic Behavior & Organization, 2020)
This paper presents a novel theoretical framework to explain the occurrence of corruption in public procurement. It extends the agency cost-padding model by Laffont and Tirole (1992) to allow for the principal to be a partially selfish politician who can design the contract auditing policy. It is found that a benevolent politician, by choosing a sufficiently strict auditing, deters the contracting firm from padding costs; conversely, a selfish politician chooses a relatively lax auditing in order to create an incentive for cost-padding, and engages in corruption with the firm in case of detection. If the cost of auditing is high enough, even a benevolent politician might prefer to allow cost-padding.
Keywords: D73; D82; L51; 330; Corruption in procurement; Cost-padding; Selfish politician; Endogenous auditing; Procurement contracts; Principal-agent model